Modern approaches on the improvement of technical skills to students who are part of the football school team in primary school - Savu Vasile Cătălin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
Using the modem methods of training in the training sessions is just one of the scientific news imposed by social changes and science breakthroughs. In this context, updating and modernizing the training process, regardless of age, is an aim determined by the need to ensure a correspondence between the content of the training and the current requirements in competitions. The purpose of the research is to improve the technical skills of the students who make up the football school team in primary school, by applying a training program based on the G.A.G. (global; analytical; global) method. The investigated sample group consists of 28 students, aged 10-11, students who make up the football school team of the schools included in the research. The experimental research took place in the 2022-2023 school year. We have made the evaluation by applying tests specific to primary education, tests held at the beginning and the end of the experiment. To measure the differences between the initial testing and the final testing we used the t (Student) test and the Wilcoxon test for independent samples. The statistical data to compare the average values were made using the SPSS for Windows. The results validate the working hypothesis and ascertain the significant progress (p <0.05) for all the tests used in evaluating the technical skills of the students in the experimental group compared to the students of the control group.